Comprehensive Diabetes Assessment Instrument for Patients With Type 2 Diabetes - Jodi Segal; Robert DeGrazia; Samantha Pitts; Kristal Brown; Maile Taualii (SAGE Publishing, 2023)
Aims: There is a paucity of efficient processes for collecting information in a primary care setting to connect patients afflicted with type 2 diabetes to valuable resources. The objective of this research project was to develop a Comprehensive Diabetes Assessment (CDA) instrument which could be used to assess patients' barriers to best outcomes. Methods: We reviewed published literature and online compilations for validated tools assessing threats to optimal diabetes self-management. We conducted focus groups with patients, clinicians, and service providers who provided feedback on the tools' appropriateness and feasibility. We aggregated the favored tools and did cognitive testing with patients to assess understanding and affective response to the instrument. Results: Five focus groups involved varied stakeholders in Baltimore, MD and Honolulu, HI. We presented 2 tools assessing knowledge barriers, 3 tools assessing psychological barriers, 4 tools assessing literacy, and 1 numeracy. The final instrument included 6 multi-part items and takes 3 minutes to complete. Cognitive interviewing with 8 patients in Baltimore and 8 in Hawaii confirmed that the instrument is understandable, quick to complete, and is acceptable to patients. Conclusions: Because of the complexity of self-management of diabetes, we suggest that this CDA instrument, plus a social needs assessment, should be administered at least annually and at times of clinical deterioration. We anticipate the instrument will be proven valuable in connecting patients to services from which they will benefit.